The effect of using Daniel's model on mathematical thinking among middle school students (The International Journal of Educational Sciences and Arts, 2025)
The current research aims to know the effect of using the Daniel model on mathematical thinking among middle school students. To achieve this goal, the researcher set the following null hypothesis: There is no statistically significant difference at a significance level of 0.05 between the average scores of the students of the experimental group who studied according to the Daniel model and the average scores of the students of the control group who studied according to the usual method in the mathematical thinking test. The research community included second-grade middle school students from the General Directorate of Education, Baghdad, Karkh III, for the academic year 2023. As for the research sample, it consisted of several students distributed between two groups, as follows: Is it warm in the experimental group and is thrown in the control group? The researcher chose the experimental design with partial control for one experimental variable, which is the Daniel model, and one dependent variable, which is mathematical thinking. The researcher matched the two groups with some variables. The research required a tool to measure the dependent variable, which is mathematical thinking. Therefore, the researcher prepared the mathematical thinking test, as the number of its paragraphs reached 17 paragraphs, 14 of which are objective and three are essay paragraphs. To verify the research hypothesis, she used the researcher used some special statistical methods, including the difficulty coefficient, the discrimination coefficient, the coefficient of effectiveness of alternatives, the Kuder-Richardson equation 20, the Cronbach alpha, and the t-test. Among the most important results reached by the research is the presence of a statistically significant difference at a significance level of 0.5% between the average scores of the experimental group students who studied according to the Daniel model and the average scores of the control group who studied according to the traditional method in the mathematical thinking test, in favor of the experimental group. In light of the research results, the researcher presented some recommendations, including using this model in teaching the rest of the mathematics subjects and teaching it at different levels and using modern models such as the Daniel model and paying attention to mathematical thinking because it is one of the goals of teaching mathematics.
Keywords: Daniel Model; Mathematical Thinking; Intermediate Stage